Cerebral Infectious Opportunistic Lesions in a Patient with Acute Myeloid Leukaemia: The Challenge of Diagnosis and Clinical Management - Gabriele Cavazza; Cristina Motto; Caroline Regna-Gladin; Giovanna Travi; Elisa Di Gennaro; Francesco Peracchi; Bianca Monti; Nicolò Corti; Rosa Greco; Periana Minga; Marta Riva; Sara Rimoldi; et al. (MDPI AG, 2024)
Central nervous system (CNS) lesions, especially invasive fungal diseases (IFDs), in immunocompromised patients pose a great challenge in diagnosis and treatment. We report the case of a 48-year-old man with acute myeloid leukaemia and probable pulmonary aspergillosis, who developed hyposthenia of the left upper limb, after achieving leukaemia remission and while on voriconazole. Magnetic resonance imaging (MRI) showed oedematous CNS lesions with a haemorrhagic component in the right hemisphere with lepto-meningitis. After 2 weeks of antibiotics and amphotericin-B, brain biopsy revealed chronic inflammation with abscess and necrosis, while cultures were negative. Clinical recovery was attained, he was discharged on isavuconazole and allogeneic transplant was postponed, introducing azacitidine as a maintenance therapy. After initial improvement, MRI worsened; brain biopsy was repeated, showing similar histology; and 16S metagenomics sequencing analysis was positive (Veilonella, Pseudomonas). Despite 1 month of meropenem, MRI did not improve. The computer tomography and PET scan excluded extra-cranial infectious-inflammatory sites, and auto-immune genesis (sarcoidosis, histiocytosis, CNS vasculitis) was deemed unlikely due to the histological findings and unilateral lesions. We hypothesised possible IFD with peri-lesion inflammation and methyl-prednisolone was successfully introduced. Steroid tapering is ongoing and isavuconazole discontinuation is planned with close follow-up. In conclusion, the management of CNS complications in immunocompromised patients needs an interdisciplinary approach.